RFID-based sensor for corrosion monitoring in concrete - Md Saad, Azezan; Abdul Rahim, Ruzairi; Ahmad, Anita; Abas, Khairul Hamimah; Mohammad Din, Shahrulnizahani (Penerbit UTHM, 2017)
All mechanical structures are subjected to deformation and cracks, due to fatigue, stress or environmental factors. Therefore it is importance to monitor the mechanical condition of critical structures in order to prevent catastrophic failures and also to minimize maintenance costs, i.e., avoid unnecessary inspections. A radio frequency identification (RFID) sensor for corrosion monitoring in concrete is presented. Corrosion of concrete reinforcement is one of the main factors leading to premature degrading of concrete structures. According to the U.S. Federal Highway Administration (FHWA), the cost of corrosion in the United States is estimated to be around $276 billion per year [1]. Besides that, reinforced concrete is one of the most widely used construction materials in the world due to its versatility and economy. Although reinforced concrete typically performs its intended use well over its service life, corrosion of steel reinforcement is a major and costly problem [2]. An analysis of the inductive coupling between the reader’s and the sensor’s antennas is carried out to guide the optimization of the RFID communication link. Linear polarization resistance measurements obtained from the developed sensor show the initiation and progression of corrosion. This paper present the RFID corrosion sensor that can read the open circuit voltage, perform linear polarization measurements, measure temperature and its own supply voltage.